Strategi Guru Dalam Meningkatkan Kemampuan Baca Al-Qur’an Pada Anak di Rumah Ngaji Umi Kalsum Medan - Arlina Arlina; A. Zeni Azima; Dea Yolanda Damanik; Nadya A.M Harahap; Nur Hidayah (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to provide an understanding to the community that the role of Qur'an teachers is so great in instilling religious character in children. By analyzing how the efforts made by the teacher in teaching the Qur'an, we will find out how much awareness and responsibility the teacher has in transferring the knowledge that exists in him to his students. The research method used is a qualitative method in a descriptive form, starting from the lack of quality of reading the Qur'an and the morality and willingness of children to study decreased. Qualitative Research is an approach in conducting a study that relies on problems in the field. The results of this study explain that the form of efforts of teachers to study in improving the ability to read the Qur'an in children is: using the talaqqi method, providing facilities without any charges, tadarrus of the Qur'an every day, providing an approach to students specifically so that they feel comfortable in learning, providing motivation and advice in the form, teachers must carry out sincere and patient intentions in providing teaching. In addition, in order to achieve the expected goals, in improving the ability to read the Qur'an, it is necessary to have aspects that support it such as, qualified teachers, teacher cooperation between peers, cooperation of parents of students, good relations with the community, and the provision of adequate facilities and infrastructure. The supporting factor in the form of the teacher's efforts to study is the support of the parents of the students and the community who are in the home environment..